2023
DOI: 10.1186/s13018-023-03573-3
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid surgery of percutaneous transforaminal endoscopic surgery (PTES) combined with OLIF and anterolateral screws rod fixation for treatment of multi-level lumbar degenerative diseases with intervertebral instability

Abstract: Background Oblique lumbar interbody fusion (OLIF) has been used to treat lumbar intervertebral instability, which has some advantages including less trauma, less blood loss, faster recovery and bigger cage. However, it usually needs posterior screws fixation for biomechanical stability, and possible direct decompression for relieving neurologic symptoms. In this study, OLIF and anterolateral screws rod fixation through mini-incision were combined with percutaneous transforaminal endoscopic surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Для хирургии дегенеративных поражений позвоночника такой подход является новаторским, так как ранее технику переднебоковой винтовой фиксации применяли только при лечении позвоночно-спинальной травмы, туберкулезных и иных поражений позвоночника [32,33]. Недостаток OLIF по сравнению с TLIF в виде невозможности выполнения прямой декомпрессии невральных структур Zhou et al [34] компенсировали симультанным проведением OLIF-AF с перкутанной эндоскопической трансфораминальной хирургией (oblique lumbar interbody fusion with lateral screw fixation and percutaneous endoscopic transforaminal discectomy -OLIF-PETD), что позволило не повреждать параспинальные мышцы, костные структуры и обеспечить минимизацию операционной травмы для пациента.…”
Section: Discussionunclassified
“…Для хирургии дегенеративных поражений позвоночника такой подход является новаторским, так как ранее технику переднебоковой винтовой фиксации применяли только при лечении позвоночно-спинальной травмы, туберкулезных и иных поражений позвоночника [32,33]. Недостаток OLIF по сравнению с TLIF в виде невозможности выполнения прямой декомпрессии невральных структур Zhou et al [34] компенсировали симультанным проведением OLIF-AF с перкутанной эндоскопической трансфораминальной хирургией (oblique lumbar interbody fusion with lateral screw fixation and percutaneous endoscopic transforaminal discectomy -OLIF-PETD), что позволило не повреждать параспинальные мышцы, костные структуры и обеспечить минимизацию операционной травмы для пациента.…”
Section: Discussionunclassified
“…The efficacy and safety of OLIF procedures have been demonstrated in many previous studies, particularly with respect to the reduction in intraoperative bleeding loss and invasive soft tissue injury, which also contribute to more rapid recovery after surgery [ 2 , 6 , 8 ]. However, undetectable blood loss, also called hidden blood loss (HBL), during OLIF procedures is often neglected by spine surgeons, resulting in unexpected postoperative complications [ 5 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] To date, some studies have compared the clinical and radiologic outcomes of OLIF with Mis-TLIF or TLIF in patients with DLS or degenerative lumbar spinal stenosis (DLSS). [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Although clinical efficacy comparable to Mis-TLIF or TLIF can be achieved, most studies have reported that posterior fixation is often required after OLIF to reduce the risk of cage displacement or subsidence. 29 However, compared with lateral fixation, posterior fixation can significantly increase OT and surgical trauma, thus making the surgery more cumbersome.…”
Section: Introductionmentioning
confidence: 99%